The Application of Probing Prompting Learning Models in Mastering Foreign Language Vocabulary - Usman, Misnawaty; Adys, Himala Praptami; Rosmaladewi, Rosmaladewi; Asnur, Muhammad Nur Ashar (International Journal of Language Education, 2023)
This study aims to obtain data about the probing prompting learning model in vocabulary mastery of the students of the Foreign Language Education Study Program, Department of Foreign Language Education, in a public university. This research is classroom action research conducted in two cycles. The subjects of this study were 30 students of the 2019/2020 Odd Semester of Foreign Language Education Study Program. The research data consists of two types, namely, qualitative data and quantitative data. Qualitative data were obtained through observation, while quantitative data were obtained through the results of the first cycle and second cycle vocabulary mastery tests. The data were analyzed using percentage techniques. The results showed that the vocabulary mastery with the percentage of values obtained by the German Language Education Study Program students in the first cycle reached 67.65%, and the second cycle reached 84.52%. These results indicate that the application of the probing-prompting learning model increases the mastery of German vocabulary for students of the German Language Education Study Program, Department of Foreign Language Education of a public university.